TEACHING SPEAKING SKILL BY USING GUIDED CONVERSATION TECHNIQUE THROUGH PAIR TAPING TO THE SEVENTH GRADE STUDENTS OF SMP PTI PALEMBANG - Herlina Herlina; Muhammad Holandiyah (Edukasi, 2015)
The objectives of the study are (1) to find out whether or not there is a significant improvement on students’ speakingability average score (2) to find out whether or not  means paired differences on students’ speaking ability who are taught by usingguided conversation technique through pair taping  higher than those who are taught by using teachers technique to the seventh grade students ofSMP PTI Palembang. The population of the study was the Seventh Grade Students of SMP PTI Palembang in the academic year of 2013/2014. The writer got the class VII.1 as the control group and VII.II as the experimental group. It consisted of 76 students, 38 students for control group and 38 students for experimental group. The result showed that teaching speaking using guided conversation technique through pair taping had a significant effect on the students’ speaking ability. It can be seen from the result of the post-test of each group. Based on the paired sample t-test analysis, it was found that t-obtained was higher than t-table. The t-obtained was 10.790 and t-table was 2.045 at the significance level p<0.05 in two-tailed testing with the degree of freedom. If t-obtain was higher than t-table, so the null hypotheses (Ho) was rejected and the alternative hypotheses (Ha) was accepted. It means that there was significant improvement in speaking ability between the students who were taught by using guided conversation technique through pair taping than those who were taught teacher’s technique.